Pengembangan Aplikasi Diagnosa Gaya Belajar dengan Pendekatan Multiple Intelligences untuk Siswa Sekolah Menengah - Yahya, Febriantoni; Muntazimah, Muntazimah (International Journal of Progressive Mathematics Education, 2025)
Each student's learning style has different tendencies. A student if he knows the tendency of his learning style, then he will do the right way so that he is more effective in learning. Diagnosis of learning styles can be done using the help of an application. By using the application one can easily learn in a style like when consulting with an expert. The type of research conducted is Research and Development (R&D). The R&D process uses the waterfall method which includes the stages of needs analysis, design, implementation and testing. The results of the study revealed that the media expert's average score was 3.04 (decent). Students' positive response to the learning style diagnosis application developed was 3.3 or 82.50% which was classified as very good.